Implementasi Metode Agile Software Development Extreme Programming pada Sistem Informasi Laboratorium Riset Zoologi - Ahmad Farhan Mahesa; Nur Hayati; Eri Mardiani (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
The Faculty of Biology and Agriculture of the National University has a zoological research laboratory that is used in terms of collecting, analyzing, and storing data on various types of organisms, laboratory services, and carrying out various lab activities such as research, publications, experiments, and research. However, there is no information system or website that can bridge the dissemination of this information. Current laboratory service management is still paper-based, such as recording book, tool, and place borrowing services where the manager must record it in a book. Therefore, an information system or website will be designed for zoological research laboratories that can assist in the dissemination of information and laboratory management using the extreme programming method. The results of the test get a positive response and in SUS testing (system usability testing) get an average score of 82 which is in the "Good" category with grade "B".